2011
DOI: 10.1007/s00595-011-0066-8
|View full text |Cite
|
Sign up to set email alerts
|

Schwannoma of the stomach with elevated preoperative serum carbohydrate antigen 19-9: report of a case

Abstract: We herein report a case of a gastric schwannoma with elevated preoperative serum carbohydrate antigen 19-9 (CA19-9) (155.2 U/ml, normal range 0-36.9 U/ml). A 59-year-old Japanese man was admitted to our hospital for treatment of a submucosal tumor of the stomach detected by barium meal, upper gastrointestinal endoscopy, and computed tomography. Endoscopic examination revealed a 3-cm diameter submucosal tumor in the antrum of the stomach, but biopsy of the lesion was unable to confirm the diagnosis. Positron em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…As a result, we believe that most GS are benign tumors that will not recur, but there are a few malignant possibilities. The histological criteria for the diagnosis of malignant schwannoma are based on mitotic map and the presence of nuclear atypia [ 20 ]. When the mitotic rate is greater than 10 / 50 high power field, it needs to be followed up regularly like other malignant tumors [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we believe that most GS are benign tumors that will not recur, but there are a few malignant possibilities. The histological criteria for the diagnosis of malignant schwannoma are based on mitotic map and the presence of nuclear atypia [ 20 ]. When the mitotic rate is greater than 10 / 50 high power field, it needs to be followed up regularly like other malignant tumors [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yang et al [21] reported a case of gastroduodenal intussusception due to GS, which, to the best of our knowledge, is the only case reported in English literature. In addition, we found only 1 case in which the patient initially presented with elevated serum carbohydrate antigen 19-9 preoperatively [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Schwannomas often occur in fourth and fifth decade and has a 1.6:1 female predilection. They are found in varied locations as the brachial plexus and the sciatic nerve [3,4,[9][10][11] . Schwannoma are slow-growing and they don't traverse the nerve but remain in sheath lying on top of it.…”
Section: Discussionmentioning
confidence: 99%